INTEGRATION OF GREEN CHEMISTRY INTO CHEMISTRY SUBJECT MATTER IN CHEMISTRY DEPARTEMENT - Suyono - (PROSIDING SEMINAR KIMIA, 2015)
This study aimed to know the readiness of chemistry students who will be pioneer and headway booster in terms of environment in their region. The measurement of students’ readinessis based on their understanding of green chemistry concept and orientation of environmental value. The data of student’s measurement used as argumentative reason to integrate green chemistry concept into chemistry subject in chemistry department. First, it was assessed by test of conceptwith certainty of response index. Second, it was assessed by questionnaire. The inferences of this study related to (1) the number of chemistry students who had wrong concept of green chemistry, who did not know the concept of green chemistry and who got misconceptions, (2) the orientation of environmental value of chemistry students was not to be expected yet, the majority were still egocentric, and (3) theintegration of green chemistry approach in the lecture had altered students environmental value to be better, their egocentric value declined while their ecocentric value increased.